2016
DOI: 10.1080/10286020.2015.1131680
|View full text |Cite
|
Sign up to set email alerts
|

Cytisine-type alkaloids and flavonoids from the rhizomes of Sophora tonkinensis

Abstract: A new cytisine-type alkaloid, (-)-N-hexanoylcytisine (1), and a new isoflavan, (3S, 4R)-4-hydroxy-7,4'-dimethoxyisoflavan 3'-O-β-d-glucopyranoside (2), along with 10 known compounds, were isolated from the rhizomes of Sophora tonkinensis. Their structures were determined by spectroscopic methods, chemical evidence, and ECD data analysis. All of the isolates were evaluated for their cytotoxic activities against four human tumor cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 16 publications
0
11
0
1
Order By: Relevance
“…There have been few studies on the genetic diversity of Sophora tonkinensis with only one report of a phylogenetic analysis within the genus Euchresta that dealt with S. tonkinensis [6]. Many studies of S. tonkinensis were limited to its phytochemical constituents and pharmacological implications [7][8][9]. Data on the genetic diversity and structure of S. tonkinensis were the foundation for developing conservation strategies, which can provide insights for better utilization and conservation of genetic resources [10].…”
Section: Introductionmentioning
confidence: 99%
“…There have been few studies on the genetic diversity of Sophora tonkinensis with only one report of a phylogenetic analysis within the genus Euchresta that dealt with S. tonkinensis [6]. Many studies of S. tonkinensis were limited to its phytochemical constituents and pharmacological implications [7][8][9]. Data on the genetic diversity and structure of S. tonkinensis were the foundation for developing conservation strategies, which can provide insights for better utilization and conservation of genetic resources [10].…”
Section: Introductionmentioning
confidence: 99%
“…In China, S. tonkinensis has been used as folk medicine to treat sore throat, acute pharyngolaryngeal infection, asthma, jaundice, and allergic dermatitis for hundreds of years [1,2]. Phytochemical investigations have shown that S. tonkinensis is rich in flavonoids [3,4,5,6,7,8], quinolizidine alkaloids [9,10,11], and arylbenzofurans [12,13]. Recent pharmacological studies have indicated that the flavonoids from S. tonkinensis showed pretty good anti-inflammatory [14,15,16], neuroprotective [17], hypoglycemic [18], anti-tumor [8,10], anti-allergic [12], and antioxidant [13] activities.…”
Section: Introductionmentioning
confidence: 99%
“…N-formyl cytisine has also been studied for medicinal purposes [11]. At present, alkaloids in congeneric plants (Euchresta) were separated only by a single method such as silica gel column chromatography, thin-layer chromatography and sephadex LH-20 [12,13], which have obvious defects, and it is difficult to achieve the purpose of systematic separation and purification.…”
Section: Introductionmentioning
confidence: 99%